Do Female CEOs Lead More Ethical Firms? ESG and Corporate Impact - Marrouche, Adnan Abdulhafiz (2025)
We study how CEO gender affects ESG disclosures and their impact on corporate policies and performance. Our results highlight a positive association between female CEOs and ESG disclosures. We also show that the conduct of female CEOs aligns more closely with stakeholder theory and has favorable implications for the relationship between ESG activities and corporate policies. Specifically, female CEOs enhance the role of ESG disclosures in increasing accounting transparency and reducing corporate risk-taking. In addition, female-led ESG initiatives positively affect both accounting and market performance. Our results highlight the heightened ethical values of female CEOs compared to their male counterparts, emphasizing their fundamental role in shaping the impact and value of ESG activities. Morally-driven ESG activities, signaling an ethical and stakeholder-friendly corporate culture, set authentic sustainability initiatives apart from mere compliance or potential window-dressing practices.